Structural design of buildings : fundamentals in design, management and sustainability - Fu, Feng; Richardson, David (Structural design of buildings series, 2024)
Structural Design of Buildings: Fundamentals in Design, Management and Sustainability is the essential reference for all structural engineers involved in the design of buildings and other structures. The book forms part of the Structural Design of Buildings series and takes a project-oriented approach, covering key issues that design professionals face at the outset of a project such as structural design processes, managing risk, loadings, sustainability, and computational design. Broken down into the key areas for understanding and undertaking structural design and with a fully international approach, this book features coverage of: design considerations; sustainability in the built environment; BIM; Risk management; different types of loadings; finite element; computational design; materials science; and concrete technology. The book contains information on collaboration with other professionals, design objectives, leadership in design, use of software and a sustainable approach to design. It is a timely and essential read for consultants, designers, technicians and contractors tasked with structural design of buildings.